The Relationship between Dual Role Conflict and Work Stress of Female Nurses - Putri, Tri Vidia Ning; Hikmatul Qowi, Nurul; Ubudiyah, Masunatul (Fundamental and Management Nursing Journal, 2023)
Introduction: Work stress is the most common problem experienced by health workers including nurses. In certain occasion, nurses did series of tasks that not in accordance with their physical abilities, expertise, and time. Therefore, stress associated works was commonly reported. The purpose of this study was to determine the relationship between dual role conflict and work stress of female nurses in the clinical setting. Methods: This study applied a cross-sectional approach. The sample was obtained by using purposive sampling. A total of 80 female nurses involved in the study . Data was conducted by self-report questionnaire sheet instrument. Descriptive and inferential statistics were applied to analyzed data. The significant level was set as p≤0.05. Results: The results indicated that the majority (66.2%) of female nurses experienced high dual role conflict, and most of them (72.5%) experienced heavy work stress. Based on the results of the Spearman Rho test, it was found that the value of p ≤0.001 (p ≤0.05) and the value of rₛ = 0.698. The current study shows strong and significant relationship between dual role conflict and work stress among female nurses. Conclusions: : In comparison to female nurses in the outpatient rooms, one day care, or other settings, those who work in inpatient ward with dual roles presented a higher workload. Stress associated with heavy workload found to be a common. Nurse managers should concern on promoting and supporting working environment by way monitoring work-load.